2005
DOI: 10.1385/ncc:3:3:237
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Stereotactic Aspiration and Thrombolysis of Spontaneous Intracerebral Hemorrhage

Abstract: In this selected cohort of patients with ICH, stereotactic aspiration and thrombolytic washout seemed to be feasible and to have a trend towards improved 30-day survival, when using their predicted mortality data as "historical control." Complications did not exceed expected incidence rates. Based on the experience presented here as well as previous similar reports, a larger, randomized study addressing dose escalation, patient selection, and best therapeutic window is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 50 publications
2
43
0
2
Order By: Relevance
“…For example, there is evidence demonstrating the safety and technical success of frameless stereotactic intracerebral hemorrhagic aspiration. [18][19][20][21] The evacuation of deep intracerebral hemorrhage requiring conventional neuro-navigational software could be further optimized by using FPCT navigation techniques. Additionally, the ability to simultaneously perform endovascular intervention opens the door to true tandem procedures, (eg, stereotactic aspiration of an epidural hematoma and meningeal artery embolization).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence demonstrating the safety and technical success of frameless stereotactic intracerebral hemorrhagic aspiration. [18][19][20][21] The evacuation of deep intracerebral hemorrhage requiring conventional neuro-navigational software could be further optimized by using FPCT navigation techniques. Additionally, the ability to simultaneously perform endovascular intervention opens the door to true tandem procedures, (eg, stereotactic aspiration of an epidural hematoma and meningeal artery embolization).…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic and endoscopic surgical evacuation of the intracerebral hematoma [56,57] or hemostatic agents [58] are being investigated. Intraparenchymal and intraventricular ultra low-dose thrombolytics to promote lysis of the hematoma are currently in phase II and III randomized clinical trials [59,60]. These interventions are all of potential therapeutic benefit in adults and, by extension, in children.…”
Section: Potential Treatments For Iphmentioning
confidence: 99%
“…It was still controversial for the effect of stereotactic aspiration of ICH (1,6,12,22). A famous trial named SICHPA (Stereotactic Treatment of Intracerebral Hematoma by means of a Plasminogen Activator) suggested that stereotactic aspiration was an effective operation to remove hematoma and improved the prognosis of patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with craniotomy, the technique of less invasive clot aspiration means the less tissue trauma. If the procedure of operation were more refined and careful, the prognosis of patients rate of mortality and improve the long-term quality of life (1,5,7,9,24). However, many researchers hold the opposite view.…”
Section: Tang Zp Et Al: Modifying the Details Of Aspiration In Patiementioning
confidence: 99%
See 1 more Smart Citation